A dynamic approach to the tendency of industries to cluster - Martin Andersson (European Regional Science Association (ERSA), 2003)
It is often stressed that industries could benefit from being co-located in space. This implies that we should be able to observe location dependencies between related industries. In this paper, the tendency of (i) manufacturing industries, (ii) input suppliers and (iii) business services to be co-located is studied. The employment in these industries is seen as being determined simultaneously, i.e. the employment in manufacturing industries is a function of the employment in business services and input suppliers and vice versa. To account for this interdependency a simultaneous-equations model à la Carlino-Mills (1989) is employed for estimation. The employment in the three industries is endogenous variables in the model. The study is based on employment data across Swedish municipalities 1993-2000. Accessibility based on time distance is incorporated into the analysis to allow for inter-municipal effects. The method allows for an assessment of the question of the tendency for these industries to cluster. Also, due to the simultaneous elements in the model, it indicates which synergy-effects are likely to take place as a result of increased employment in one of the industries, which is important from a policy perspective.
Keywords: 330